Modern methods for quality control of cosmetic and dermatological materials containing nanoparticles - Rakhimova, M. V.; Бондаренко, І. С.; Yaremenko, V. D.; Sych, I. A.; Kobzar, N. P.; Perekhoda, L. O. (My University, 2024)
The work is devoted to modern methods of quality control of cosmetic and dermatological materials containing nanoparticles. A new acoustic-magnetic method for determining the concentration of nanoparticles is considered, thanks to which the calculated dependences of the physical parameters of ultrasound, magnetic nanoparticles, the colloidal medium, the magnetic detector, and the concentration of nanoparticles in the studied medium were obtained, and the minimum detected concentration of magnetic nanoparticles was estimated up to 10 -7 vol. %.
Keywords: nanoparticles; acoustic-magnetic method; magnetic field